“Wow! I Have Six Fingers!”: Would You Accept Structural Changes of Your Hand in VR? - Hoyet, Ludovic; Argelaguet, Ferran; Nicole, Corentin; Lécuyer, Anatole (Frontiers in Robotics and AI, 2016)
With the increasing demand in virtual reality applications and games, the need to understand how users perceive their virtual representation (avatar) is becoming more and more important. In particular, with the potential of virtual reality to alter and control avatars in different ways, the user representation in the virtual world does not always necessarily match the user body structure. In this context, this paper explores how users would accept as their own a six-digit realistic virtual hand. By measuring participants’ senses of ownership (i.e., the impression that the virtual hand is actually our own hand) and agency (i.e., the impression to be able to control the actions of the virtual hand), we somehow evaluate the possibility of creating a Six-Finger Illusion in VR. We measured these two dimensions of virtual embodiment in a virtual reality experiment where participants performed two tasks successively: (1) a self-manipulation task inducing visuomotor feedback, where participants mimicked finger movements presented in the virtual scene and (2) a visuotactile task inspired by Rubber Hand Illusion protocols, where an experimenter stroked the hand of the user with a brush. The real and virtual brushes were synchronously stroking the participants’ real and virtual hand, and in the case when the virtual brush was stroking the additional virtual digit, the real ring finger was also synchronously stroked to provide consistent tactile stimulation and elicit a sense of embodiment. Results of the experiment show that participants did experience high levels of ownership and agency of the six-digit virtual hand as a whole. We found higher levels of ownership and agency for the additional finger when the hand was fully animated, compared to a control group where the additional digit was not animated. Through the presented experiment, we found that participants responded positively to the possibility of controlling the six-digit hand despite the structural difference, and accepted the six-digit virtual hand and individual digits as their own to some extent. These results bring preliminary insights about how avatar with structural differences can affect the senses of ownership and agency experienced by users in VR.